Evolution of the incidence of type 1 diabetes mellitus in the Community of Madrid, 1997-2016 - Honorato Ortiz-Marrón; Virginia del Pino Valero; María Esteban-Vasallo; Belén Zorrilla Torras; María Ordobás Gavín (Elsevier, 2021)
Introduction: The objective of this article was to estimate the type 1 diabetes mellitus (T1DM) incidence in the child population of the Community of Madrid (CM) and its evolution between 1997 and 2016, using the medical-administrative data of the regional registry of T1DM. Methods: T1DM cases of children under 15 years of age, reported to the regional registry or collected from secondary sources were included: Spanish Diabetics Association (1997−2013), and from 2014 on the Basic Minimum Data Set (BMDS). Annual incidence rates were estimated per 100 000 person-years. The comparison of the rates was analysed using Poisson regression models using incidence ratios (IR). Results: A total of 2658 cases were identified as new diagnoses of T1DM. The mean incidence rate for 1997−2013 was 13.7 cases per 100 000 person-years. In the 2014−2016 period, 20 cases per 100 000 persons-years were registered using the BMDS. The age group with the highest incidence was 10−14 years in the two periods (16.6 vs. 25.5). In boys, the age with the highest incidence was 10-14 years in both periods (17.9 vs 30.4), and in girls, the age of 5-9 years (17.0 vs 25.1). Incidence rates decreased slightly in both genders until 2013 (from 15.0 to 11.6). In 2014−2016, the annual incidence rate varied between 18.4 and 21.1 cases (IR: 1.77). The incidence remained stable in children under 5 years old and increased from 5 to 14 years old. Conclusions: The CM is among the regions with a high incidence of T1DM. In its first phase, the regional registry underestimated the incidence of T1DM, and with the incorporation of the MBDS as a source of information, the estimates for the second period (2014−2016) are possibly closer to the actual incidence of T1DM. The data presented suggests the need to know the real evolution of the incidence of the disease by incorporating computerised health records. Resumen: Introducción: El objetivo fue estimar la incidencia de diabetes mellitus tipo 1 (DM1) en la población infantil de la Comunidad de Madrid (CM) y su evolución entre 1997 y 2016, a partir de los datos médicos-administrativos del registro regional de DM1. Métodos: Fueron incluidos los casos de DM1 de menores de 15 años, notificados al registro regional o captados de fuentes secundarias: Asociación Diabéticos Españoles (1997−2013) y a partir de 2014 del Conjunto Mínimo Básico de Datos hospitalario (CMBDS). Se estimaron tasas de incidencia anual por 100.000 personas-año. La comparación de las tasas se analizó mediante modelos de regresión de Poisson a través de razones de incidencia (RI). Resultados: Un total de 2658 casos fueron identificados como nuevos diagnósticos de DM1. La tasa de incidencia media de 1997−2013 fue de 13,7 casos por 100.000 personas-año. En el periodo 2014−2016, utilizando el CMBDS se registraron 20,0 casos por 100.000. El grupo de edad con mayor incidencia fue el de 10−14 años en los dos periodos (16,6 vs 25,5). En los niños, la edad de mayor incidencia fue de 10 a 14 años en ambos periodos (17,9 vs 30,4) y en las niñas el de 5 a 9 años (17,0 vs 25,1). Las tasas de incidencia descendieron ligeramente en ambos sexos hasta 2013 (de 15,0 a 11,6); en 2014-2016 la tasa de incidencia anual varió entre 18,4 y 21,1 casos (RI: 1,77). La incidencia permaneció estable en menores de 5 años y aumentó de 5 a 14 años. Conclusiones: La CM se sitúa entre las regiones de alta incidencia de DM1. En su primera fase, el registro regional infraestimaba la incidencia de DM1. Con la incorporación del CMBDS como fuente de información, las estimaciones del segundo periodo (2014−2016) son posiblemente más próximas a la incidencia real de DM1. Los datos que presentamos sugieren la necesidad de conocer la evolución real de la incidencia de la enfermedad incorporando los registros digitales sanitarios.